Treatment of Class II malocclusion with Forsus appliance: a long-term assessment - Brito, Deborah Brindeiro de Araújo (2020)
Introduction: Successful treatment of Class II Division 1 malocclusion is implied to the long-term stability of treatment changes. Objective: The research aimed to evaluate the outcomes of Class II division 1 malocclusion correction with Forsus Fatigue Resistant Device (FRD) and the long-term stability of skeletal, dentoalveolar and occlusal changes produced by this therapy, associated to the patient satisfaction in the long-term. Material and Methods: 14 patients who were evaluated at 3 stages: pretreatment (T1), posttreatment (T2) and long-term posttreatment (T3) stages. The subjects also answered a satisfaction questionnaire at T3. Intragroup comparison of the cephalometric variables and the PAR index T1, T2 and T3 were were performed with ANOVA, followed by Tukey tests. Intragroup comparison of the OGS index at T2 and T3 were performed with dependent t tests. Intergroup comparisons of posttreatment changes and normal growth changes of the treatment group were performed with t tests. Results: There were dentoskeletal and soft tissue changes favorable for class II malocclusion correction. PAR index improved with treatment (T2- T1) and both PAR and OGS indexes remained stable at the long-term posttreatment period (T3-T2). Treatment has remained stable after 5 years follow-up. Conclusions: Treatment with the Forsus FRD appliance is efficient for patients with Class II malocclusion and changes obtained during treatment remained stable in the long-term posttreatment. The vast majority of patients were satisfied with the treatment and the current smile esthetics.